2004
DOI: 10.1021/es0305611
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Hexahydro-1,3,5-trinitro-1,3,5-triazine in Aqueous Solutions

Abstract: Electrochemical reduction of RDX, hexahydro-1,3,5-trinitro-1,3,5-triazine, a commercial and military explosive, was examined as a possible remediation technology for treating RDX-contaminated groundwater. A cascade of divided flow-through cells was used, with reticulated vitreous carbon cathodes and IrO2/Ti dimensionally stable anodes, initially using acetonitrile/water solutions to increase the solubility of RDX. The major degradation pathway involved reduction of RDX to the corresponding mononitroso compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 23 publications
(37 reference statements)
3
53
0
1
Order By: Relevance
“…RDX is considered a possible class C carcinogen and also affects the central nervous system in mammals [14]. A number of efforts have been made to determine the fate of RDX in the environment and to develop technologies for remediation of RDX contaminated soil and groundwater, including thermal degradation; photo- and chemical oxidation/reduction; alkaline hydrolysis, adsorption, free radical and biodegradation [12, 18–19, 23, 31, 3334, 38, 41, 46–48, 52, 55–56, 59, 7274, 8991]. Knowledge of molecular structure, transformation mechanisms and range of potential RDX intermediates and products is necessary to management of contaminated real estate, particularly where military personnel are involved.…”
Section: Cyclic Nitraminesmentioning
confidence: 99%
“…RDX is considered a possible class C carcinogen and also affects the central nervous system in mammals [14]. A number of efforts have been made to determine the fate of RDX in the environment and to develop technologies for remediation of RDX contaminated soil and groundwater, including thermal degradation; photo- and chemical oxidation/reduction; alkaline hydrolysis, adsorption, free radical and biodegradation [12, 18–19, 23, 31, 3334, 38, 41, 46–48, 52, 55–56, 59, 7274, 8991]. Knowledge of molecular structure, transformation mechanisms and range of potential RDX intermediates and products is necessary to management of contaminated real estate, particularly where military personnel are involved.…”
Section: Cyclic Nitraminesmentioning
confidence: 99%
“…Bonin et al [42] showed that RDX is readily decomposed to small molecules upon galvanostatic reduction in acetonitrile/water solutions. A flow-through divided cell reactor was employed, with a membrane as separator between anode and cathode, and the test solution was passed through several times until the substrate was consumed.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…The reduction of energetic compounds such as TNT, and RDX and there kinetic transformations in separate electrode compartments are discussed by [1012]. The in-situ use of direct electrochemical (e − barrier) for the removal of RDX and TNT were studied in column studies by [13,14] by sequential anode and cathodes with an electric potential 5 to 10 volts under constant current of 10 and 20 mA.…”
Section: Introductionmentioning
confidence: 99%